CUSTOMS INTERMEDIARIES AS AN INSTITUTIONAL COMPONENT OF THE SYSTEM OF FOREIGN TRADE REGULATION OF UKRAINE - DZIUBYNSKYI, Andrii; PAKHOLIUK, Olena; DZIUBYNSKA, Oksana; MELNIKOVA, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the role of customs intermediaries as an institutional element of Ukraine’s foreign trade regulation system. Customs brokerage activities are an integral part of modern customs administration and a key mechanism that ensures effective interaction between business entities and customs authorities. The paper identifies the main functions of customs intermediaries, including the preparation and submission of customs declarations, calculation of customs payments, execution of customs formalities, documentation management, and legal consulting. It is established that customs brokers contribute to simplifying customs procedures, reducing clearance time, and preventing violations of customs legislation, which directly influences the efficiency of Ukraine’s foreign trade. The study highlights the historical evolution of the customs brokerage institute in Ukraine, from its formation in the 1990s to the present stage of digital transformation. Special attention is given to the implementation of electronic systems such as the “Single Window for International Trade,” the “National Transit System (NCTS),” and “e-Customs,” which optimize document exchange and enhance transparency in cross-border operations. The research identifies current challenges in the development of customs intermediation, including fragmented legislation, insufficient digital integration, lack of unified professional standards, and limited access to international customs information platforms. The article substantiates key directions for improving the efficiency of customs intermediaries’ activities in Ukraine — harmonization of national legislation with the EU Customs Code, introduction of professional certification for brokers, and expansion of digital tools for trade facilitation. The results prove that customs intermediaries play a strategic role in ensuring transparent and efficient foreign trade regulation and are a driving force for Ukraine’s integration into the European customs and economic space.